Palm-oil transformation into green and clean biofuels: Recent advances in the zeolite-based catalytic technologies - Gunawan, Melia L.; Novita, Tria H.; Aprialdi, Faisal; Aulia, Deaul; Nanda, Arxhel S.F.; Rasrendra, Carolus B.; Addarojah, Zaqiyah; Mujahidin, Didin; Kadja, Grandprix T.M. (Bioresource technology reports, 2023)
Fossil fuels are still the most used fuel in industrial activities and transportation. Coal consumption as the mainly used fossil fuel increases yearly, increasing pollutants such as CO2, NOX, SO2, and other particulate matter. On the other hand, biofuels as green fuels have a prospective future as an alternative fuel to replace fossil fuels. Biofuels can be classified based on their raw materials into four generations. Biofuels can be produced through many kinds of technologies, such as transesterification and cracking, deoxygenation, and isomerization with the presence of H2 or not called hydro and non-hydro processes. Zeolite is one of the most compatible heterogeneous catalysts for these processes due to its excellent properties, such as good catalytic activity, selectivity due to its unique shape, microporosity and mesoporosity properties, long lifetime, and good reusability. The potential of zeolite is significantly increased when combined with several oxides. [Display omitted] •Palm oil as prospective feedstock in biofuel production•Zeolite as heterogenous catalyst and its potential in biofuel productions•Recent technologies for biofuel production including hydro and non-hydro process•The synthesis route and comparison of each technology for biofuels production